2007
DOI: 10.5957/jsr.2007.51.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nonlinear Ship Model Parameters Based on the Turning Circle Test

Abstract: This work presents a contribution to solving the problem of identification of ship model parameters using the experimental results from a particular trial test. The innovation of this paper lies in the fact that for this identification purpose it is necessary to know only the turning radius that describes the ship during the performance of the turning test trial. A relatively complex nonlinear model of Norrbin has been chosen as a basis because it represents the ship's dynamics appropriately, as proven through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several studies on predicting ship maneuvers are presented in the recent literature and that can be divided into two steps: state & parameter estimation and trajectory prediction. Various state & parameter estimation approaches in ship navigation are proposed by the following studies with the respective methods: linear continuous time domain model with discrete time measurements [13], Kalman filter [14], extended Kalman Filter and Second Order Filter [15], nonlinear Norrbin model [16], non-linear ship maneuvering mathematical model [17], Support Vector Regression (SVR) [18], and recursive neural networks ( [19] - [20]). Similarly, various trajectory prediction approaches in ship navigation are proposed by the following studies with the respective methods: neural networks [21], Maneuvering Modeling Group (MMG) standard method [22], autoregressive moving average (ARMA) and neural networks [23].…”
Section: A Mathematical Modelsmentioning
confidence: 99%
“…Several studies on predicting ship maneuvers are presented in the recent literature and that can be divided into two steps: state & parameter estimation and trajectory prediction. Various state & parameter estimation approaches in ship navigation are proposed by the following studies with the respective methods: linear continuous time domain model with discrete time measurements [13], Kalman filter [14], extended Kalman Filter and Second Order Filter [15], nonlinear Norrbin model [16], non-linear ship maneuvering mathematical model [17], Support Vector Regression (SVR) [18], and recursive neural networks ( [19] - [20]). Similarly, various trajectory prediction approaches in ship navigation are proposed by the following studies with the respective methods: neural networks [21], Maneuvering Modeling Group (MMG) standard method [22], autoregressive moving average (ARMA) and neural networks [23].…”
Section: A Mathematical Modelsmentioning
confidence: 99%
“…Muske et al [20] identified a nonlinear dynamic model of an unmanned vessel using parameter estimation data from towing experiments. Haro Casado et al [21] proposed a four-parameter identification algorithm for ship models based on adaptive processes and backstepping theory. This work makes a contribution to solving the problem of parameter identification for ship models based on experimental results.…”
Section: Introductionmentioning
confidence: 99%